Pulmonary infection with mycobacterium xenopi: review of treatment and response. - Banks, J (1984)
Forty seven patients (82% male) with pulmonary infection caused by Mycobacterium xenopi have been reviewed. Pre-existing lung disease was present in 35 (75%). In 21 patients the disease was characterised by a subacute illness developing over a period of two to four months, while in another 20 patients there was a longer history of chronic respiratory problems often associated with slowly progressive changes evident from chest radiographs. Response to treatment was poor and unpredictable, and was not related to the results of in vitro sensitivity tests, pre-existing lung disease, or mode of onset of symptoms. Eleven patients (23%) were cured with chemotherapy. The best drug regimen appeared to be rifampicin and isoniazid combined with either streptomycin or ethambutol. Another 12 (26%) showed favourable responses to drug treatment initially, but eventually relapsed. Four patients had progressive disease while receiving prolonged courses of chemotherapy. Resection was performed in five patients with resultant cure in four. Since the prognosis with drug treatment alone is so unpredictable it is suggested that resection might be part of first line treatment, and that it should usually be performed if patients fail to respond to initial chemotherapy or if they relapse.